Prudential Regulation and Banking Risk in MENA Countries (Global Journal of Management and Business Research, 2018)
This paper analysis the impact of prudential regulation on banking risk using the measurement technique "z-score" by introducing the financial and economic determinants (real GDP growth rate, inflation, real GDP growth rate, inflation, the governance indicator, etc.). For this reason, we used a sample of 146 conventional banks in the MENA region during the 2003-2014 period, whose purpose was to determine the specificities of these countries about the determinants of banking risk.
Keywords: banking regulation; banking risk; z-score; mena countries